THE PENGARUH INOVASI TEKNOLOGI TERHADAP KEPUASAN PELANGGAN YANG DIMEDIASI OLEH KUALITAS PELAYANAN - Anwar Sulaiman (Lensa, 2023)
This study aims to analyze the effect of technological innovation on customer satisfaction through service quality both directly and indirectly on Tokopedia application users in Bogor City. The purposive sampling technique was used to determine the research sample so that 210 Tokopedia application users were obtained. The results prove that technological innovation directly has a positive and significant effect on service quality so that to improve service quality Tokopedia can innovate by Discontinuous innovations can be radical innovations or completely new innovations. Technological innovation has a positive and significant effect on customer satisfaction, to increase customer satisfaction Tokopedia can increase Responsiveness, namely providing fast (responsive) and precise service to customers with clear information delivery. Service Quality has a positive and significant effect on customer satisfaction, Willingness to recommend both to family, friends, and others is very important because it is a free promotion that will greatly benefit Tokopedia in increasing customer satisfaction. The indirect effect value is greater than the direct effect value, which means that service quality is able to mediate the effect of technological innovation on customer satisfaction.